P-66 Contribution factors of end-of-life care options for patients in south east asian cohort. (1st September 2015) - Wong, Jane CQ; Lau, Cindy SL; Tan, SH; Tan, BC; Ng, CSH; Lim, SM; Wong, G; Sim, KLD
Abstract : Background: Our institution has implemented advance care planning (ACP) for cardiac inpatients since 2013. Aim: To explore main contributing factors influencing patients' choice of end-of-life (EOL) care options. Methods: Patients hospitalised for heart failure, arrhythmia, myocardial infarction were enrolled from 1st June 2013 to 30 th November 2014. Results: 112 patients were enrolled from a screening of 1943 patients. Out of 112 patients, 69 (61.6%) had completed ACP discussions. 57 (82.6%) patients chose comfort care (CC) whereas 12 (17.4%) chose life-sustaining treatments (LST) for their EOL care. Mean age for CC patients is 62.3 and mean age for LST patients is 59.7. 86.0% patients who chose CC stay with their family compared to 91.7% patients in LST. 49.1% of CC patients are unemployed whereas 83.3% of LST patients are unemployed. 68.4% of CC patients are married compared to 58.3% of LST patients. 10.5% of CC patients had no education compared to 25% of LST patients. 19.3% of CC patients had no religion compared to 8.3% of LST patients. No difference in gender distribution (77.2% for CC patients vs 75.0% for LST patients). More Chinese patients opted for CC (96.5% vs 75.0% in LST patients). Discussion: Patients who chose CC are generally older, employed, married, educated, Chinese race compared to LST. Majority of CC group prefer quality of life to quantity of life, and do not want to burden family due to length, cost of treatments and emotion endurance. Conclusion: Patient's EOL care options are contributed by multiple factors like age, education, race, employment status and marital status.